Developing quality assessment elements for tree planting works / Jasasikin Ab Sani - Ab Sani, Jasasikin (2015)
Malaysia is experiencing a major change in landscape development. In relation to the aim of turning Malaysia into ‘Garden Nation’, various strategies have been mapped including the campaign of greening the country through optimizing the number of tree planted over the country. Millions of trees have already been planted and many more will be planted in order to achieve a target of twenty millions of trees by the year of 2020. Despite the fact that the campaign is successfully carried out, the issue of quality for tree planting work still need to be duly addressed. The government of Malaysia under the Quality Management System (QMS) programme through Construction Industry Development Board (CIDB) in the year of 2006, has established Quality Assessment System in Construction (QLASSIC) as a tool to measure the quality of construction work. QLASSIC is a system or method to measure and evaluate the quality of workmanship of a construction work based on the relevant approved standard. QLASSIC enables the quality of workmanship between construction projects to be objectively compared through a scoring system. The aim of this study is to develop a set of quality assessment elements for landscape works which focusing on tree planting to be a part of an important components to facilitate QLASSIC program for landscape work. The development of quality assessment elements for tree planting was carried out through the survey on Landscape Architects' opinions on the level of Critical success factors of landscape work element. The opinion of Landscape Architects was gathered through five ordinal value or likert-type scale of every element. The data were then been used to develop a weightage for every element based on Contribution Weightage Formula. The findings reveal that soi 1-mixture, root ball and planting hole are the elements that are ranked as the three most critical elements for the success of tree planting work. Finishing & treatment, staking and mulching are among the three elements that have been ranked as three lowest critical success factors for tree planting works. It is hoped that the findings would help to facilitate the QLASSIC in addressing quality assessment for landscape work. Besides, the findings can be a reference in the process of betterment the quality documents for landscape work in Malaysia.